2022 Social Accounting Matrix for Rwanda - International Food Policy Research Institute (International Food Policy Research Institute, 2024)
The 2022 Rwanda Social Accounting Matrix (SAM) follows IFPRI's Standard Nexus SAM approach, by focusing on consistency, comparability, and transparency of data. The Nexus SAMs available on IFPRI's website separates domestic production into 42 activities. Factors are disaggregated into labor, agricultural land, and capital, with labor further disaggregated across three education-based categories. The household account is divided into 10 representative household groups: Rural and urban households across per capita consumption quintiles. Nexus SAMs support the improvement of model-based research and policy analysis in developing countries and allow for more robust cross-country comparisons of national economic structures, especially agriculture-food systems.